"We have this awesome organization where it was built by women for women like us": Supporting African American women through their pregnancies and beyond. (3rd July 2019) - Hmiel, Laura; Collins, Cyleste; Brown, Portia; Cherney, Emily; Farmer, Christin
ABSTRACT: Infant mortality is a problem that disproportionately affects infants of African American women, particularly residents in underserved neighborhoods. Chronic stress due to racism has been identified as an important factor in infant mortality. This study examined a novel community-based perinatal support professional (PSP) program, Birthing Beautiful Communities (BBC), in Cleveland, Ohio. BBC provides services for pregnant African American women in underserved neighborhoods with the goal of decreasing infant mortality and low birthweight rates by addressing chronic stress. Focus groups and one individual interview were conducted with the program's 14 PSPs, and 25 clients were interviewed individually. Interviews were analyzed inductively using qualitative thematic analysis to identify pervasive themes. Coders identified major themes of stress, resilience, community, cultural matching, advocacy, self-care, transformation, and self-actualization. BBC PSPs and clients alike reported the program is transforming the lives of clients by helping them address stressors. Findings suggest the community-based PSP model is an important but underused intervention in addressing infant mortality.